Polonistyka na Uniwersytecie Karola w Pradze – historia i współczesność - Rusin Dybalska, Renata (Postscriptum Polonistyczne, 2020)
The article dwells on a history of Polish Studies at Charles University in Prague, starting from the very beginning of courses till the present day. The Polish Studies have always been an important element of Slavonic education; currently they are a part of Central European Studies. The article is concerned with the research interests of the polonists of Prague and it reveals structures and directions the polonistic education aims at and is undertaking within the Chair of Central European Studies.